Hydrological Characterization of Kusa Mining Hill, Ijero-Ekiti Nigeria, Using Geo-Electrical and Electromagnetic MethodsHydrological Characterization of Kusa Mining Hill, Ijero-Ekiti Nigeria, Using Geo-Electrical and Electromagnetic Methods - Alu, Olatunji O.; Ologe, Oluwatoyin; Ogungbemi, Samuel O. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2015)
An integrated electromagnetic and geo-electric study was carried out in some parts of Kusa Mountain, Ijero Ekiti, Southwest Nigeria. Very Low Frequency Electromagnetic (VLF-EM) profiling was measured along eight traverses from which conductive (fractured) zones were established. This enabled the location of 10 points at prominent fractured zones where vertical electrical sounding (VES) were conducted to further reveal the geo-electric parameters. The electromagnetic and geo-electric parameters were analysed, processed and modeled with relevant software in order to obtain the spatial distribution of the groundwater. From the groundwater potential map, the study area was rated as low, moderate and high groundwater potential. This study showed that central to eastern region fell within high groundwater zone. The region around VES 8 and 9 (northeastern flank) was rated as moderate while the remaining part is rated as having low groundwater potential. It is recommended that future exploration and exploitation work for groundwater resources should be concentrated around region rated as having high groundwater potential